Depiction of an Ascetic and a Surasundari - Temples of India Project Team (Jio Institute, 2024)
The details of the rear or eastern wall of the garbhagriha (sanctum sanctorum) illustrate the contrast between the ascetic and the surasundari (celestial damsel). The ascetic (on the left) is characterized by a substantial jatabhara (braided hairdo) atop his head, a lengthy beard, and a moustache. His elongated earlobes signify the mahapurusha lakshana (markers of a great individual). His bare upper body is adorned with a broad yajnopavita (sacred thread), with a langot (loincloth) covering his lower body. Despite the apparent damage and raised position of his right hand, his left-hand holds an unidentified object. The damaged surasundari figure, on his right, stands gracefully with a voluptuous body adorned with exquisite ornaments. Though her raised right hand is damaged, she holds a fine scarf in her left hand near her belly, draping it around her arms. Her lower body is covered by a translucent garment so delicate that her body underneath is visible. A small creature is depicted climbing her left leg. In stark contrast to the tranquil and composed posture of the ascetic, the surasundari vividly embodies sensual beauty. Notably, there is a kalasha (pitcher) placed at the bottom near her feet, surrounded by foliage symbolizing abundance and growth, mirroring the symbolism of the female body.